A Novel Technique for Synchronous Laparoscopic Splenectomy and Azygoportal Disconnection With Hepatectomy. (June 2018) - Jiang, Guoqing; Bai, Dousheng; Chen, Ping; Qian, Jianjun; Jin, Shengjie
Background. Liver resection was not formerly recommended in patients with both hepatocellular carcinoma (HCC) and portal hypertension because of difficult perioperative bleeding control and postoperative liver failure. Splenectomy is a proven method with which to overcome these problems. To investigate the safety and feasibility of synchronous laparoscopic splenectomy and azygoportal disconnection with hepatectomy (LSDH) for treatment of portal hypertension accompanied with HCC, we describe a clinical cohort of 10 patients who underwent a new technique of synchronous LSDH. Methods. A cohort of 10 cirrhotic patients with HCC, esophageal/gastric variceal bleeding, and hypersplenism received LSDH. A 6-port method was used for LSDH. This procedure comprises 5 steps: laparoscopic splenectomy, intraoperative splenic blood salvage, laparoscopic azygoportal disconnection, laparoscopic partial hepatectomy, and removal of spleen and liver specimens. Intraoperative autologous cell salvage was performed before hepatectomy. Results. LSDH was successful in all patients. There was no conversion to open operations. The operative time was 220.5 ± 19.8 minutes, blood loss was 264.0 ± 160.3 mL, and postoperative hospital stay was 10.2 ± 1.8 days. Conclusions. Selective synchronous LSDH is a feasible, effective, and safe surgical procedure with satisfactory short-term efficacy. It is a promising minimally invasive treatment option for patients with cirrhotic HCC and portal hypertension.